The Effect of Product Photograph and Information on Digital Apparel Marketing - (:unkn) unknown (PACIFIC INST MANAGEMENT, 2021)
The aim of this study is to reveal whether consumers are affected by product information and product photographs while purchasing pants from digital channels. The study consists of two stages. In the first stage, an online survey that evaluated the effect of the purchase behavior of pants pants photographs and information, was performed on 651 young consumers in Turkey. According to SPSS analysis, important results were obtained for the difference in the demographic factors of the consumers and the criteria that affect the purchasing of the consumer are determined. In addition, it was concluded that information about the size of the trousers, fabric content, coloring, waist size, slackness, suitability for the use of wide-calfed consumers are also the criteria related to apparel information that affect the purchasing decision of the consumer. In the second stage of the research, three websites were scanned. The photos and information of the pants in the e-market places that consumers prefer most when purchasing apparels were examined according to the criteria determined in the first stage of the research. As a result of the examination, it was concluded that the pants photos and pants information in the relevant e-marketplaces did not meet some criteria that young consumers attach importance to. As a result of this research, which supports quantitative analysis with visual evidence, valuable advice has been given to the digital marketing sector.
Keywords: Digital marketing; consumer behaviour; apparel; marketing; consumer choice; ONLINE